Some Identities on the 𝑞-Integral Representation of the Product of Several 𝑞-Bernstein-Type Polynomials - Taekyun Kim (Abstract and Applied Analysis)
The purpose of this paper is to give some properties of several 𝑞-Bernstein-type polynomials to express the 𝑞-integral on [0, 1] in terms of 𝑞-beta and 𝑞-gamma functions. Finally, we derive some identities on the 𝑞-integral of the product of several 𝑞-Bernstein-type polynomials.